INTEGRATING SOCIAL ENTREPRENEURSHIP AND ADAPTIVE LEADERSHIP IN STRENGTHENING INCLUSIVE MSMEs - Dunggio, Titin; Hamzah, Ariyati; Airmas, Meylani; Tumampas, Putri Adtirah; Karim, Cindrawati H. (Jurnal Ilmu Manajemen dan Bisnis, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as the backbone of Indonesia’s economy, contributing significantly to Gross Domestic Product (GDP) and employment absorption. However, MSMEs continue to face major challenges, such as limited access to capital, technology, markets, and a low adaptive capacity in responding to the dynamic business environment. In this context, social entrepreneurship and adaptive leadership emerge as innovative approaches with great potential to enhance the resilience and inclusivity of MSMEs. Social entrepreneurship emphasizes the simultaneous creation of social and economic value, while adaptive leadership enables organizations to innovate amid uncertainty. This study aims to comprehensively analyze how the integration of these two approaches can strengthen inclusive MSMEs in Indonesia, using a systematic literature review method of accredited national journals. The findings reveal that their integration generates a strong synergy, promoting financial sustainability alongside social impact, such as empowering vulnerable groups and increasing business resilience. Practically, MSME actors are encouraged to adopt impact-based business models and develop adaptive leadership capacities. Meanwhile, policymakers are advised to formulate support frameworks that foster innovation and inclusion. Theoretically, this research enriches the literature on inclusive entrepreneurship by proposing an integrative model that aligns with the context of developing countries. Further empirical research is recommended to validate the proposed model.